2019
DOI: 10.3390/app9214618
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Methods for Reduction of the High Stress of Ultra-High Asphalt Concrete Core Dams

Abstract: With the rapid development of asphalt concrete core rockfill dams (ACCRDs), the construction of ultra-high asphalt concrete core rockfill dams (UACCRDs) has been improved significantly. However, the security problems of asphalt concrete core (ACC) become very prominent with the increase of dam height. The shear failure control standard and tensile failure control standard of ACC are suggested. The mechanisms of ACC that generate high shear stress and high tensile stress are investigated. Based on the definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The calculation results show that as the slope of the left bank becomes steeper, the stress level and shear stress S13 component of the core decrease. The maximum stress level is located in the left bank near the bottom area, and there is also a large area of high stress level in the middle of the right bank, which is consistent with the conclusion of the reference [30] . The rock on the left bank is steep and the core has a large misalignment along the bank slope.…”
Section: In Uence Of Joint Form Under Asymmetric Valley Conditionsupporting
confidence: 89%
See 2 more Smart Citations
“…The calculation results show that as the slope of the left bank becomes steeper, the stress level and shear stress S13 component of the core decrease. The maximum stress level is located in the left bank near the bottom area, and there is also a large area of high stress level in the middle of the right bank, which is consistent with the conclusion of the reference [30] . The rock on the left bank is steep and the core has a large misalignment along the bank slope.…”
Section: In Uence Of Joint Form Under Asymmetric Valley Conditionsupporting
confidence: 89%
“…The study shows that there is a signi cant shear effect between the core and the bank slope due to the constraints of the valley terrain. In order to quantify the magnitude of shear action, [12] proposed the shear safety control standard of ACC based on the stress characteristics of ACC in different periods. In general, the current research on ACCRDs at home and abroad is mainly aimed at the general valley terrain, and there are few studies on the impermeability and safety of the joint between the asphalt core and the base under the condition of high-steep bank slopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some researchers have recently used FEM for identifying the static and dynamic behavior of an asphaltic concrete rockfill dam [20,21]. Wu et al (2018) found that the stress distribution and deformation of the asphaltic core are appropriate during the completion and operating stages and do not cause shear failure in the asphaltic core or hydraulic failure.…”
Section: Introductionmentioning
confidence: 99%